PERUBAHAN TARIF UANG WAJIB TAHUNAN BADAN PENGUSAHAAN BATAM TAHUN 2016: TINJAUAN EKONOMI POLITIK - Siregar, Achyar Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Annual mandatory money is land lease money which must be paid by applicant of land allocation (individual, investor, and or legal entity) to Batam Indonesia Free Zone Authority (BIFZA). In 2016, Bifza changes annual mandatory money tariff which is accorded by Head Regulation Number 19 of 2016. Problems are between rejection of society elements, worsening economic downturn, without coordination with interested sides, and threat of harm to workers. This research have two aims first, it is identifying and explaining the causes of annual mandatory money tariff change. Second, it is identifying and explaining the profit and loss of BIFZA annual mandatory money tariff change. This research uses the theory of rational choice and the theory of public choice as a theoretical framework.This research uses descriptive qualitative approach. The data is collected by informants purposively. Data collection technique uses field research, interview, and documentation study. Data analysis uses reduction process, presentation, and data verificationThe result of this research shows first, annual mandatory money tariff change in 2016 caused by Finance Ministry Regulation Number 153/PMK.05/2012 change to Finance Ministry Regulation Number 148/PMK.05/2016, consideration of time span with irrelevant old annual mandatory money tariff, and adjustmentitation of Value of Tax Object have gaps. These three causes are unilateral action by BIFZA without coordination with stakeholders in Batam. Second, the beneficiary sides are BIFZA because it gains high revenues from land users, and foreign investors because annual mandatory money tariff does not put a burden on them in reducing investment gap with domestic investors. The harmed sides are community, businessmans, and workers because limited people purchasing power toward expensive annual mandatory money tariff, large investment burden, and trigger of employment termination by the company.Keywords: Annual Mandatory Money, Batam Indonesia Free Zone Authority, Political Economy.